AGAMA DAN PRILAKI PRO LINGKUNGAN PADA SISWA PASANTREN DAN SISWA SMA - safrilsyah, Safrilsyah safrilsyah; Sattar, Syibran Mullasi; Ulfah, Marina; julianto, Rahmad (Faculty of Ushuluddin and Humanities, 2024)
Environmental issues are increasingly urgent, highlighting the need for pro-environmental behavior, especially among students. This study aims to examine the role of religion and differences in pro-environmental behavior between Islamic boarding school students and public school students. A quantitative approach with comparative techniques was used. The measuring instrument was the Pro-Environmental Behavior Scale by Larson et al. (2015). The sample consisted of 221 students selected from a population of 643 using probability sampling with a cluster sampling technique. The results showed a significant difference in pro-environmental behavior (t = 6.689, p = 0.000), with Islamic boarding school students scoring higher (Mean = 112.5; SD = 13.6) than public school students (Mean = 101.6; SD = 9.7). These findings suggest that the religious-based educational environment contributes to shaping students’ environmental awareness. A clean and religious educational setting plays an important role in fostering greater concern for the environment among students.